2016
DOI: 10.1515/aiht-2016-67-2776
|View full text |Cite
|
Sign up to set email alerts
|

Terbufos-sulfone exacerbates cardiac lesions in diabetic rats: a sub-acute toxicity study

Abstract: Organophosphorus compounds (OPCs) have a wide range of applications, from agriculture to warfare. Exposure to these brings forward a varied kind of health issues globally. Terbufos is one of the leading OPCs used worldwide. The present study investigates the cardiac effect of no observable dose of a metabolite of terbufos, terbufos-sulfone (TS), under nondiabetic and streptozotocin-induced diabetic condition. One hundred nanomoles per rat (1/20 of LD 50 ) was administered intraperitoneally to adult male Wister… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 29 publications
1
3
0
Order By: Relevance
“…The parameters lipase, insulin, and glycemia are much higher in OP-exposed diabetic subjects; this suggests that exposure to organophosphorus pesticide form a gravity factor for diabetic's conditions. Our results are in concordance with earlier studies (85,86). The Cameroonian population is much more sensitive to this variation compared to the Pakistani population; for example, the lipase value is 197.67 in OP-exposed diabetic subjects in the Cameroonian population against 179.02 in the Pakistani population.…”
Section: Butyrylcholinesterase (Bche)supporting
confidence: 92%
“…The parameters lipase, insulin, and glycemia are much higher in OP-exposed diabetic subjects; this suggests that exposure to organophosphorus pesticide form a gravity factor for diabetic's conditions. Our results are in concordance with earlier studies (85,86). The Cameroonian population is much more sensitive to this variation compared to the Pakistani population; for example, the lipase value is 197.67 in OP-exposed diabetic subjects in the Cameroonian population against 179.02 in the Pakistani population.…”
Section: Butyrylcholinesterase (Bche)supporting
confidence: 92%
“… Organophosphate studied Model animal Dose, route and duration of exposure Signs of cardiotoxicity Reference Terbufos-sulfone Male Wister rats 1/20 of LD 50 /day, intraperitoneal, 15 days Damaged mitochondria of cardiomyocytes. Nurulain et al, 2016 Dichlorvos Wistar rats 8.8 mg/kg, oral, 21 days Lack of striations, myocardial hemorrhage and necrosis-like features detected in heart tissues; Cardiac cholesterol, low-density lipoprotein, atherogenic and atherosclerotic indices were elevated. Imam et al, 2018 Fenthion Sprague-Dawley rats 0.8 g/kg, subcutaneous, 24 h Elevated levels of Troponins and myocardial injury, including edema, inflammation, vacuolization and necrosis.…”
Section: Cardiotoxicitymentioning
confidence: 99%
“…The collected blood was divided into two tubes for subsequent analysis for plasma and serum fractions, using EDTA coated and plain glass tubes respectively. The blood was centrifuged at 3500 rpm for 10 min at 25 [7,59] have previously shown that cholinesterase activities particularly AChE can be used as a marker to measure acute and/or chronic exposure to OPs pesticides. RBC-acetylcholinesterase (RBC-AChE) and butyrylcholinesterase (BChE) activities were determined according to Worek et al [60] using Specord 50 plus spectrophotometer (Number; 233H1280C, Analytic Jena, Jena, Germany).…”
Section: Study Design and Recruitment Of Study Subjectsmentioning
confidence: 99%
“…Insecticides have also been linked to human DNA damage, multiple degenerative diseases, and cancer [ 3 , 4 , 5 ]. Organophosphates (OPs) are one of the widely used pesticides (more than 50% of world consumption) globally and their use is expected to increase even more in coming years, with the direct consequence of increased health problems [ 6 , 7 ]. Adverse health effects of OPs have been attributed predominantly to their systemic actions, i.e., they block the degradation of acetylcholine at cholinergic synapses by irreversible inhibition of acetylcholinesterase (AChE) and butyrylcholinesterase (BChE) [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%